Anaplasma, Bartonella, and Rickettsia infections in Daurian ground squirrels (Spermophilus dauricus), Hebei, China - Xue, Jing; Chen, Si-Si; Xu, Ze-Yun; Wang, Fang-Ni; Wang, Jiangli; Diao, Danhong; Du, Luanying; Xie, Guang-Cheng; Guo, Wen-Ping (Frontiers in Microbiology, 2024)
Rodents have been confirmed as hosts of various vector-borne zoonotic pathogens and are important for the maintenance of these microbes in nature. However, surveillance for zoonotic pathogens is limited for many wild rodent species in China, so our knowledge of pathogen ecology, genetic diversity, and the risk of cross-species transmission to humans is limited. In this study, 165 spleen samples of Daurian ground squirrels (Spermophilus dauricus) were collected from Weichang Manchu and the Mongolian Autonomous County of Hebei Province, China, and Rickettsia, Bartonella, and Anaplasma were identified by DNA detection using polymerase chain reaction (PCR). Sequence analysis identified eight bacterial pathogens: R. raoultii, R. sibirica, Candidatus R. longicornii, B. washoensis, B. grahamii, B. jaculi, A. capra, and Candidatus Anaplasma cinensis. Co-infection of B. grahamii and R. raoultii in one sample was observed. Our results demonstrated the genetic diversity of bacteria in Daurian ground squirrels and contributed to the distribution of these pathogens. Six species, A. capra, R. raoultii, R. sibirica, Candidatus R. longicornii, B. washoensis, and B. grahamii, are known to be pathogenic to humans, indicating a potential public health risk to the local human population, especially to herders who frequently have close contact with Daurian ground squirrels and are thus exposed to their ectoparasites.